2020
DOI: 10.1080/0144235x.2020.1777705
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment at vapour–liquid interfaces of mixtures: establishing a link between nanoscopic and macroscopic properties

Abstract: Component density profiles at vapour-liquid interfaces of mixtures can exhibit a non-monotonic behaviour with a maximum that can be many times larger than the densities in the bulk phases. This is called enrichment and is usually only observed for low-boiling components. The enrichment is a nanoscopic property which can presently not be measured experimentally -in contrast to the classical Gibbs adsorption. The available information on the enrichment stems from molecular simulations, density gradient theory, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 201 publications
5
53
0
Order By: Relevance
“…Results from equilibrium molecular thermodynamics show an enrichment of low-boiling components at vapour-liquid interfaces for many mixtures [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. This enrichment is predicted consistently by molecular simulations, i.e.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Results from equilibrium molecular thermodynamics show an enrichment of low-boiling components at vapour-liquid interfaces for many mixtures [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. This enrichment is predicted consistently by molecular simulations, i.e.…”
Section: Introductionmentioning
confidence: 72%
“…This enrichment is predicted consistently by molecular simulations, i.e. Monte Carlo (MC) or molecular dynamics (MD) simulations, as well as density gradient theory (DGT) [46,47,52,53,[66][67][68]. Since the enrichment is a nanoscopic effect at fluctuating fluid interfaces, currently no experimental methods are available to study it directly.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Today, molecular dynamics (MD) simulations are employed extensively in the petroleum industry, which can reveal some interfacial properties of multiphase systems at the molecular level [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Stephan et al, investigated the vapor–liquid interface properties of binary mixtures (cyclohexane + CO 2 ) via MD simulations [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paint atomization in air spraying process is one of the complex issues about gasliquid two-phase flows. There are some complex phenomena such as evaporation of organic solvent components in the paint and mass transfer through the vapour-liquid interface of mixtures during the atomization process [5]. Colbert et al [6] found that the solvent evaporation from a droplet is negligible due to the short flight time by mass transfer calculations.…”
Section: Introductionmentioning
confidence: 99%